Tenth Five Year Plan (2002-2007) and Annual Plan (2003-2004) Government of Himachal Pradesh - Planning Commission (Planning Commission, 2002)
Himachal Pradesh has the privilege of snowfed perennial rivers and rivulets flowing in almost all parts of the Pradesh. Yamuna, with its important tributaries of Tons, Pabbar and Giri in the east and Satluj, Beas, Ravi and Chenab in the west flow through various parts of the Pradesh. Some of the important natural lakes worth mentioning are Khajjiar, Ghadasasu Lamba Dal, Manimahesh, Mahakali in Chamba Distt.; Dal, Kareri in Kangra Distt.; Rewalsar, Kumarwah, Prashar in Mandi district; Bhrigu and Dashahr in Kullu Distt.; Chandratal and Surajtal in Lahaul & Spiti Distt.; Chandra Naun in Shimla district; and Renuka in Sirmaur Distt.
Planning Department, Government of Himachal Pradesh